2011
DOI: 10.1089/jayao.2011.0040
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Physical Activity Intervention Targeting Young Adult Cancer Survivors

Abstract: Young adults who have been treated for cancer face several health and psychosocial risks. To minimize these risks, is it imperative that they address any modifiable risk factors, such as sedentary lifestyle. Unfortunately, more than half of young adult cancer survivors remain sedentary. To facilitate the adoption of physical activity (PA) in this population-potentially reducing health and psychosocial risks-we developed and pilot tested an internet-based PA intervention for young survivors. Eighteen young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(154 citation statements)
references
References 42 publications
3
147
1
Order By: Relevance
“…However, greater improvements in moderate to vigorous physical activity were observed here. Prior studies have observed improvements in moderate to vigorous physical activity that ranged from 18-minutes [24] to 103-minutes [30], whereas we observed a 250-minutes increase in our complete-case and 147-minute increase in our intent-totreat analyses. Despite the large improvements we observed, the effect size comparing conditions were small in magnitude.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…However, greater improvements in moderate to vigorous physical activity were observed here. Prior studies have observed improvements in moderate to vigorous physical activity that ranged from 18-minutes [24] to 103-minutes [30], whereas we observed a 250-minutes increase in our complete-case and 147-minute increase in our intent-totreat analyses. Despite the large improvements we observed, the effect size comparing conditions were small in magnitude.…”
Section: Discussioncontrasting
confidence: 94%
“…Our feasibility data were favorable, but attrition rates were high. The study's attrition rate was comparable to previous web-based intervention studies [48][49][50], but higher than others [24,26,[29][30][31]34]. We believe that functionality challenges contributed to high attrition rates.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The high enrollment rate of YAs who were in early treatment confirms their willingness to participate in PA studies, which is consistent with earlier studies indicating that YA survivors are interested in learning about PA. 18,19 The study completion rate of 71% is within range of PA studies with older adult cancer patients during treatment 3 and somewhat lower than other longitudinal studies with YA survivors of AYA cancers. [19][20][21] As a measure of functional capacity, the 6MWT was easy and safe for the YAs to complete. Their walk distances showed a wide range of exercise capacity-as low as 50% and as high as 90%-when compared to healthy persons of comparable age, gender, height, and weight.…”
Section: Discussionmentioning
confidence: 76%
“…Careful readings of the 22 full manuscripts further reduced the field to nine studies that met all inclusion criteria. [33][34][35][36][37][38][39][40][41][42] Of these studies, six included adolescent survivors, two addressed young adult survivors only, and one included both young adult and adolescent survivors. Interventions were heterogeneous across study design (nonrandomized, noncontrolled versus randomized, controlled trial), sample sizes (range =10-251), ages (range =3-39 years of age), diagnoses (acute lymphoblastic leukemia [ALL], brain tumor, mixed diagnoses), and points of intervention (on-treatment, immediate postcompletion of treatment, long-term survivorship).…”
Section: Exercise Strategies In Aya Cancer Survivors -A Review Of Thementioning
confidence: 99%